Pengembangan media Scrapbook Berbasis Konteks Budaya Suku Sasak Pada Pembelajaran IPS Siswa Kelas IV SDN 1 Sakra Selatan - Isnawati, Isnawati; Gunayasa, Ida Bagus Kade; Zain, Muh. Irawan (Pendagogia: Jurnal Pendidikan Dasar, 2022)
Abstrak: This study aims to determine the steps of making media and to determine the feasibility of scrapbook media based on the cultural context of the Sasak tribe in social studies learning for grade IV students at SDN 1 Sakra Selatan. The type of research used in this research is research and development (R&D) with the design steps of the ADDEI model developed by Endang Mulyatiningsih 2019. Data collection methods in this study used multiple choice tests, questionnaires, and documentation. The result of this study is that scrapbook media is suitable for use as a learning medium. The result of this research is that scrapbook media is suitable to be used as a learning medium. Based on the results of the validation of media experts obtained 95% and the results of the validation results by material experts 90%. After the validation test was carried out by the media and material experts, the researcher carried out the application using a multiple choice test. It could be seen that the result of the average pretest score in the experimental class was 5,333.3%, which was greater than the average value for the pretest in the control class, which was 5,167%. Meanwhile, the average score on the post-test test in the experimental class was 8,333.3%, which was greater than the average score for the post-test in the control class, which was 8,333.3%. it can be concluded that the scrapbook media is very valid and the student's response is very good so that the media is very suitable to be used as a learning medium. Keywords: Development, Meida Scrapbook, Sasak Cultural Context, and Social Studies Learning.